2004
DOI: 10.1179/135100004225006830
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of reactive oxygen species generation in synovial fluid from patients with temporomandibular disease by electron spin resonance spectroscopy

Abstract: Reactive oxygen species (ROS) have been implicated in the pathogenesis of temporomandibular disorders. In the present study, we provide the first evidence of ROS generation in the synovial fluid from human temporomandibular disorder patients, as shown by electron spin resonance (ESR) and spin trapping. Three distinct ESR spectra of DMPO spin adducts were observed in the synovial fluid. They corresponded to three free radical species: hydroxyl radical (HO(*)), hydrogen radical (H(*)), and carbon-center radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Interestingly, these results are consistent with the ESR spectra obtained from SF in the TMD patients (Fig. 4) [7].…”
Section: Ros Production In Synovial Fluid From Tmd Patientssupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, these results are consistent with the ESR spectra obtained from SF in the TMD patients (Fig. 4) [7].…”
Section: Ros Production In Synovial Fluid From Tmd Patientssupporting
confidence: 93%
“…We have developed an ESR-based technique to detect free radical reactions in biological system in vitro or in vivo. Using the ESR-spin trapping technique, we have previously demonstrated that hydroxyl radical (HO ) could be generated by catalytic reaction of H 2 O 2 with free iron ions (Fenton reaction) in the IL-1a-induced TMJ rat arthritis model or in synovial fluid (SF) of the TMD patients [6,7]. In the present review, we discussed the oxidative stress related to the pathogenesis of the TMD, and demonstrate that the improvement of the oxidative stress would raise the possibility of constructing novel treatment strategies for TMD.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper our aim was mature chondrocytes culture not for multiplication but for the study of the effects of anoxia/ re-oxygenation, which is considered to occur in vivo (James et al, 1990;McIlwraith, 1996;Dimock et al, 2000;Lee et al, 2004). We cultured the cells under 5% or 21% O 2 , as regulated in the gas phase, with variable glucose concentrations: 0 g/L as an extreme condition, 1.0 g/L similar to in vivo conditions (Liberg et al, 1977), and 4.5 g/L because this glucose concentration is commonly used for the culture of articular chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Although, that studies allowed understand the mechanisms of pathophysiology of the TMJ disorders, and give the assumption for treatment approach. There are also possibilities of applying the electron spin resonance (ESR) in diagnosis of reactive oxygen species (ROS) in the synovial fluid from temporomandibular disorder patients [34]. ROS correspond to free radical species and could exacerbate the inflammatory process and activate the cartilage matrix degrading enzymes, what leads to OA.…”
Section: Discussionmentioning
confidence: 99%